Ligustilide Prevents Radiation Enteritis by Targeting Gch1/BH4/eNOS to Improve Intestinal Ischemia - Yan, Tao; Guo, Shun; Zhang, Tian; Zhang, Zhimin; Liu, An; Zhang, Song; Xu, Yuan; Qi, Yuhong; Zhao, Weihe; Wang, Qinhui; Shi, Lei; Liu, Linna (Frontiers in Pharmacology, 2021)
There is a high incidence of radiation enteritis (RE) after abdominal radiotherapy. The occurrence of RE seriously affects the treatment and quality of life of patients; however, its pathogenesis is complex and there are no effective drugs for its prevention or treatment. Intestinal ischemia plays an important role in the occurrence of enteritis. Previous studies have shown that targeting GTP-cyclohydrolase 1 (Gch1) to improve intestinal ischemia could be a new strategy to prevent and treat RE. A high content of the naturally occurring phthalide derivative ligustilide (LIG) has been found in the plant drug Rhizoma Ligustici Chuanxiong for the treatment of cardiovascular diseases. The purpose of this study was to evaluate the protective effects of LIG on RE. Ionizing radiation (IR) rat and endothelial cell models were used to observe and record rat body weights and stool morphologies, measure intestinal blood perfusion by laser Doppler blood flow imaging, determine the diastolic functions of mesenteric arteries, detect the levels of Gch1/BH4/eNOS pathway-related proteins and regulatory molecules in the mesenteric arteries and endothelial cells, and predict affinity by molecular docking technology. The results showed that LIG significantly improved the body weights, loose stools, intestinal villi lengths, intestinal perfusion and vasodilatory functions of IR rats. LIG also significantly improved Gch1 protein and BH4 levels in the mesenteric arteries and endothelial cells after IR, increased the NO content, reduced superoxide accumulation, and improved p-eNOS (Ser1177) levels in endothelial cells. LIG has good affinity for Gch1, which significantly improves its activity. These results indicate that LIG is the preferred compound for the prevention and treatment of RE by improving intestinal ischemia through the Gch1/BH4/eNOS pathway. This study provides a theoretical basis and new research ideas for the development of new drugs for RE.